Use of AI as a Research Recruitment Tool: A DSMB Perspective. - Barnbaum, Deborah R. (American Journal of Bioethics, 2026)
The article focuses on the implications of using artificial intelligence (AI) for participant recruitment in clinical trials from the perspective of data safety monitoring boards (DSMBs), also known as data safety monitoring committees (DSMCs). It highlights the potential benefits of AI in enhancing recruitment efficiency, reducing bias, and improving trial completion rates, which align with DSMB goals of protecting participants and ensuring scientific integrity. However, the article emphasizes challenges related to AI’s explainability, reliability, and oversight, recommending that researchers maintain transparency about AI use and that DSMBs incorporate AI expertise to properly evaluate recruitment algorithms. It also notes potential difficulties in expanding DSMB membership due to limited AI experts and varying opinions on adding specialized members, while underscoring the importance of early integration of such expertise to safeguard participant welfare.